Prevalence of tobacco dependence among rural population of Mysuru District - H. P., Poorvitha; Kumar D., Sunil; Basava J., Dodda (International Journal Of Community Medicine And Public Health, 2023)
Background: Tobacco is generally a leaf with 1-3% of the alkaloid nicotine Consuming it becomes so dangerous that it is the leading cause of mortality worldwide. Tobacco risks include heart attack, gum disease and pre-cancerous mouth lesions etc. The purpose of the current study is to investigate the prevalence of Tobacco dependence and factors that contribute to tobacco dependence among rural populations. Objectives of current study was to estimate the prevalence of tobacco dependence and to assess the factors influencing Tobacco dependence among rural population. Methods: A community based cross sectional study was carried out in rural areas of Nanjangud taluk for 6months from January 2022 to June 2022. Multistage sampling Technique was adopted to select the study population.one subcentre is selected randomly by lottery method, PPS sampling technique will be applied to select the required number of participants from the villages in the selected subcentre. Sample size is 362 individuals aged above 18years who comes under ICD10 criteria were included in the study. The data were gathered using the pre-tested, semi-structured questionnaire by interview method, and the FRAGESTROM test to assess dependence on nicotine SPSS version 25 was used for analysis. Results: The overall prevalence of Tobacco dependence among rural population of Nanjangud taluk is 62.40%. We found that tobacco dependence was significantly associated with gender, age group, occupation education, and socioeconomic status and there is no significant association between caste and Tobacco dependence. Conclusions: The present study concludes that the prevalence of tobacco dependence is high in a rural population. More tobacco free initiatives to be implemented.